Kedudukan Rezim Internasional dalam Hukum Internasional Kontemporer - Rivaldo Ganti Diolan Siahaan (Jurnal Hukum Lex Generalis, 2021)
Nowadays, in addition to the existence of countries as exclusive actors in international relations, many are also non-countries that become actors in international relations. Likewise against international regimes, but the status of international regimes in international law is not clear until now. This journal uses normative-based research by using conceptual approach as the backing of research. The results stated that the international regime in a single capacity is not the subject of international law but its embodiment as an international organization that is the subject of international law. The position of international regimes in contemporary international law in the form of cooperation in the form of international treaties can be a source of international law. In the form of institutions in the form of international organizations can be the domiciled subject of international law.